Under pressure - Nursing staff's perspectives on working hours and recovery during the COVID-19 pandemic: A qualitative study - Isabelle Hernandez; Marie Söderström; Ann Rudman; Anna Dahlgren (Elsevier, 2024)
Background: The COVID-19 pandemic contributed to increased pressure on healthcare systems. During periods when the demands exceed the capacity of healthcare organizations, adaptive strategies are used to meet these demands. During the COVID-19 pandemic, working hours for nursing staff were reorganized and extended. This has posed challenges for recovery, which may be a key factor for maintaining health and safety under such conditions. Objectives: The aim of the study was to bring insights into how nursing staff perceived their working hours and recovery during the COVID-19 pandemic, and if they experienced any changes in their sleep and well-being. Design: A qualitative descriptive design was chosen, as it is suitable for gaining insight into perceptions and experiences. Methods: Qualitative semi-structured interviews were conducted using an interview guide. The interviews were analyzed using thematic analysis. Sixteen registered nurses and six certified nursing assistants from four Swedish hospitals participated in the study. Results: The organization of working hours during the COVID-19 pandemic was considered suboptimal and resulted in more demanding working hours and poor recovery. Nursing staff experienced loss of control as they lost influence over working hours, working hours became more unpredictable and the boundaries between work and leisure became blurred. Nursing staff also experienced a decline in their health and well-being, including extreme fatigue, impaired sleep and physical/mental changes. Conclusion: The strategies used by healthcare organizations to meet increasing demands during the COVID-19 pandemic contributed to impaired recovery and well-being of nursing staff, which could generate negative feedback loops contributing to depletion of resources at the organizational level.